Effectiveness of Oral Sensory-Motor Stimulation in Premature Infants in the Neonatal Intensive Care Unit (NICU) Systematic Review - Paula Rodriguez Gonzalez; Veronica Perez-Cabezas; Gema Chamorro-Moriana; Carmen Ruiz Molinero; Ana María Vazquez-Casares; Gloria Gonzalez-Medina (MDPI AG, 2021)
The aim of this study was to identify and to assess the best evidence currently available on the effectiveness of oral sensory-motor stimulation in preterm infants in the neonatal intensive care unit. We performed a systematic review following the Preferred Reporting Items for Systematic Reviews (PRISMA) statements. The search was conducted using the Pubmed, Web of Science (WOS), PEDro and Scopus databases. Clinical trials were reviewed and PEDro rating scale was used to assess the methodological quality of these studies. Results: 1267 studies were found and 11 were relevant and included in this review. Improvements were obtained in achieving independent feeding, maturation of the sucking pattern, transition to full feeding, motor function and length of hospital stay in most studies. Conclusions: there is evidence to support the benefits of the use of oral sensorimotor stimulation to achieve independent oral feeding in preterm infants, thereby reducing their stay in the Neonatal Intensive Care Unit.